Cytochrome P450 3A expression and function in liver and intestinal mucosa from dexamethasone-treated sheep - Maté, María Laura (2012)
The effects of repeated administrations of dexamethasone (DEX) (3mg/kg/day by IM route for 7days) on the gene expression profile of a cytochrome P450 (CYP) 3A28-like isoenzyme, on the expression of a CYP3A-immunoreactive protein and on CYP3A-dependent metabolic activities in sheep liver and small intestinal mucosa were evaluated in the current work. CYP 3A-dependent metabolic activities (erythromycin and triacetyl-oleandomycin N-demethylations) were assessed in microsomal fractions. The mRNA expression of CYP3A28-like, glucocorticoid receptor, constitutive androstane receptor, pregnane X receptor and retinoic X receptor alpha (RXRα) was determined by quantitative real-time PCR. The expression of a CYP3A-immunoreactive protein was measured by Western blot analyses. In the liver, DEX treatment increased CYP3A28-like mRNA levels (2.67-fold, P<0.01) and CYP3A apoprotein expression (1.34-fold, P<0.05) and stimulated CYP3A-dependent metabolism. High and significant correlation coefficients between CYP3A-dependent activities and CYP3A28-like gene (r=0.835-0.856, P<0.01) or protein (r=0.728-0.855, P<0.05) expression profiles were observed. Among the transcriptional factors, DEX only stimulated (2.1-fold, P<0.01) the mRNA expression of RXRα. In sheep small intestine, DEX caused a slight increment (34.6%, P<0.05) in erythromycin N-demethylase activity in the jejunal mucosa and a significant enhancement (P<0.05) of CYP3A apoprotein level in the duodenal mucosa.